Characteristics of diagnostic defects in traumatic brain injury (forensic medical approach) - Pletenetska, A. (Journal of Education, Health and Sport, 2023)
Diagnostic defects in the evaluation of TBI, such as the violation of protocols, neglect of neurological symptoms, and incorrect description of head injuries, can significantly impact the diagnosis and forensic assessment of TBI. The study of defects in the provision of medical care in traumatic brain injury (TBI) was conducted based on the data from forensic medical examinations of Kharkiv Regional Bureau of Forensic Medical Examination (KhRBFME) (307) and SI "Main Bureau of Forensic Medical Examination of the Ministry of Health of Ukraine" (SI MBFME) (226). The largest number of undiagnosed diagnostic and treatment measures related to clinically mild forms of TBI due to incomplete description of the neurological status, failure to consider the complete neurological symptomatology specific to a particular form of TBI, diagnosis based solely on subjective complaints of the patient and historical data (head injury, according to the patient's words), lack of patient examination by related specialists, and absence of additional investigations. Significant defects influencing the forensic medical assessment of TBI in the affected individuals included: incomplete description of neurological symptomatology (91±2.4%), absence of trauma history (23.5±1.8%), defects in describing external head injuries (67.9±2.0%), simulation, and aggravation.